Sporadic leucodystrophy with neuroaxonal spheroids: persistence of DWI changes and neurocognitive profiles: a case study. Issue 6 (22nd February 2010) - Mateen, Farrah J; Keegan, B Mark; Krecke, Karl; Parisi, Joseph E; Trenerry, Max R; Pittock, Sean J
Abstract : Leucodystrophy with neuroaxonal spheroids (LNS) is rare. There have been fewer than 10 sporadic cases reported, all occurring in the fourth to sixth decades of life. Previously unreported diffusion weighted imaging (DWI) changes on brain imaging in LNS are described as well as the first neurocognitive profile of this disorder in a 24-year-old woman. Neuropsychological testing demonstrated a global cognitive decline, with deficits most representative of a frontal-subcortical dementia. Bright DWI and corresponding dark apparent diffusion coefficient changes were initially mistaken for acute cerebral infarction but then persisted for 19 weeks. Biopsy of a bright DWI lesion showed no evidence of vascular disease and confirmed this rare diagnosis. Given the number of patients with the diagnosis of cerebrovascular disease, supported by DWI findings, we propose other milder cases of LNS may be overlooked.